2009
DOI: 10.1259/bjr/12568539
|View full text |Cite
|
Sign up to set email alerts
|

National reference doses for common radiographic, fluoroscopic and dental X-ray examinations in the UK

Abstract: The National Patient Dose Database (NPDD) is maintained by the Radiation Protection Division of the Health Protection Agency. The latest review of the database analysed the data collected from 316 hospitals over a 5-year period to the end of 2005. The information supplied amounted to a total of 23 000 entrance surface dose measurements and 57 000 dose-area product measurements for single radiographs, and 208 000 dose-area product measurements along with 187 000 fluoroscopy times for diagnostic examinations or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
168
5
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(198 citation statements)
references
References 6 publications
8
168
5
5
Order By: Relevance
“…DRLs for cervical spine AP and LAT using DAP measurements were not reported in NRPB and other studies 7 , 27 Table 6 shows that the first DRLs for these are 0.16 and 0.25 Gy.cm 2 , respectively.…”
Section: Discussionmentioning
confidence: 64%
“…DRLs for cervical spine AP and LAT using DAP measurements were not reported in NRPB and other studies 7 , 27 Table 6 shows that the first DRLs for these are 0.16 and 0.25 Gy.cm 2 , respectively.…”
Section: Discussionmentioning
confidence: 64%
“…DAP values are related to fluoroscopy time, fluoroscopy output and filtration, diameter of image intensifier and kVp-mA values. Measured values may be compared to reference values reported for certain procedures (7). In adolescent idiopathic scoliosis, Schaefer et al (15) reported mean DAP values of 94.9 cGy.cm 2 for conventional AP full spine radiographs and 7.8 cGy.cm 2 for the fluoroscopic scanning method.…”
Section: Resultsmentioning
confidence: 99%
“…The normalKa,r in children were smaller than those for adults due to the automatic selection of fluoroscopy technique triggered by the smaller patient size. The fluoroscopy examinations were performed with longer time and higher KAP, resulting in large effective doses (Table 3) that were also broad with respect to the measured values as compared to the available values in the literature 2 , 9 , 10 , 11 , 12 , 13 , 14 , 15 . The IDRLs for the normalKa,r, KAP, and fluoroscopy time, especially in children, were not available in the cited literature for comparison.…”
Section: Discussionmentioning
confidence: 99%
“…These quality assurance challenges are exacerbated by emerging health needs and lack of adequate resources coupled with the ballooning population. This study aimed to determine the radiation dose to patients, establish the necessary optimization strategies for fluoroscopy procedures, and compare the findings with the international DRLs 2 , 9 , 11 , 12 , 13 , 14 , 15 …”
Section: Introductionmentioning
confidence: 99%